Correlation of Normal Labor and Vacuum Extraction with Postlabor Stress Urinary Incontinence : Hubungan Cara Persalinan Normal dan Vakum Ekstraksi dengan Stres Inkontinensia Urin Pascasalin - Beni Gunawan; Bobby I. Utama (Indonesian Socety of Obstetrics and Gynecology, 2020)
Objective: To determine the correlation between normal delivery methods and vacuum extraction with postpartum stress urinary incontinence in West Sumatra.Methods: This study used cross-sectional study design in the Obstetrics and Gynecology Department of the RSUP Dr. M. Djamil Padang, network hospital and Puskesmas in Padang City from October 2018-February 2019. The sampling technique was consecutive sampling. Urinary stress incontinence were assessed using a questionnaire for urinary incontinence diagnosis (QUID).Results: There was a correlation between normal delivery and vacuum extraction with stress urinary incontinence after delivery in the province of West Sumatra (p <0.05).Conclusion: There is a correlation between normal labour and vacuum extraction with stress urinary incontinence after delivery in the province of West Sumatra.Keywords: normal labour, stress urinary incontinence, vacuum extraction Abstrak Tujuan: Mengetahui hubungan cara persalinan normal dan vakum ekstraksi dengan stress inkontinensia urin pascasalin di Provinsi Sumatera Barat.Metode: Penelitian ini menggunakan desain potong lintang di Poliklinik Bagian Obstetri dan Ginekologi RSUP Dr. M Djamil Padang, RS jejaring dan Puskesmas di Kota Padang sejak bulan Oktober 2018-Februari 2019, Teknik pengambilan sampel dengan consecutive sampling. Penilaian stress inkontinensia urin dengan menggunakan questionnaire for urinary incontinence diagnosis (QUID).Hasil :Terdapat hubungan persalinan normal dan vakum ekstraksi dengan stress inkontinensia urin pascasalin di provinsi Sumatera Barat (p<0,05).Kesimpulan : Penelitian menyimpulkan terdapat hubungan persalinan normal dan vakumekstraksi dengan stressinkontinensia urin pascasalin di provinsi Sumatera Barat.Kata kunci: persalinan normal, stres inkontinensia urin, vakum ekstraksi